2021
DOI: 10.21203/rs.3.rs-152763/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimization of Fermentation Conditions for Recombinant Lipase Expression At Small Scale Using Response Surface Methodology for Preliminary Production In Two Bioreactor Platforms.

Abstract: Background: Pseudomonas lipases are widely used in industrial applications due to its unique biochemical properties, but one of the biggest limitations are the low yields obtained in native strains therefore, organisms as E. coli are used for the recombinant lipase overexpression. However, the recombinant lipase is accumulated as inclusion bodies and it affects biological activity, making that researchers evaluate different fermentation conditions to improve the activity of recombinant enzymes. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…This difference might occur due to the different sizes of the plasmid. Another study by López et al (2021) used the E. coli BL21(DE3) strain and estimated the μmax at three different temperatures of 5, 15, and 25 o C in LB. They concluded that increasing the temperature, increased the μmax to a maximum level of 0.16 h -1 at 25 o C, which is lower by 0.12 h -1 than the μmax reported in this study at 27 o C, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This difference might occur due to the different sizes of the plasmid. Another study by López et al (2021) used the E. coli BL21(DE3) strain and estimated the μmax at three different temperatures of 5, 15, and 25 o C in LB. They concluded that increasing the temperature, increased the μmax to a maximum level of 0.16 h -1 at 25 o C, which is lower by 0.12 h -1 than the μmax reported in this study at 27 o C, i.e.…”
Section: Discussionmentioning
confidence: 99%